Indigenous Sovereignty Is Under Attack as Supreme Court Bends Rules for Settlers - Nagle, Rebecca (Truthout, 2024)
In the past 30 years, Indigenous tribes and tribal interests have lost two-thirds of all United States of America Supreme Court cases.
United States of America